Draft Annual Plan 1964-65 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1963)
In the year 1963-64. the Planning Commission had approved an outlay of Rs. 89.36 crores, which was, however, raised to Rs. 92.34 crores after further discussions with the Adviser, Planning Commission. The outlay was increased without asking for any increase in the total assistance of Rs. 57.60 crores indicated by the Commission. Subsequently. Agriculture and allied programmes in the current year’s Plan were examined in greater detail by the Central Study Team on Agriculture with a view to accelerating the pace of schemes relating to agricultural production.
Planning Department, Government of Uttar Pradesh